UPAYA PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN MELALUI METODE STRUKTURAL ANALITIK SINTETIK (SAS) DI KELAS II SEKOLAH DASAR - Nuraqidah, Sridewi; Sutisnawati, Astri; Rizqia Amalia, Arsyi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to use the Synthetic Analytical Structural (SAS) approach to improve the early reading skills of second graders at SDN Sawahlega. The goal was to engage the kids in reading exercises, starting with the SAS method. This study, which was conducted across two cycles, falls under the category of classroom action research (CAR), in which the teacher serves as the researcher. The framework for the research was influenced by the model proposed by Kemmis and McTaggart. The participants of the study included 35 students from the second grade. To gather data, various methods such as tests, observation forms, and documentation were utilized. Descriptive statistical analysis was employed for data evaluation. The findings revealed that implementing the SAS approach, along with guidance and the use of letter cards, positively affected the early reading capabilities; in the initial assessment, 57% of students passed with an average score of 72. Following the first cycle, the average score rose to 79, yielding a 69% passing rate. By the second cycle, the average score had further risen to 85, yielding an 80% passing rate. These findings show that the SAS approach successfully improves second graders' early reading abilities at SDN Sawahlega.